Influence of solid surface, temperature and concentration on contact angle of water-FeC nanofluid. (November 2021) - Huminic, Angel; Huminic, Gabriela; Fleaca, Claudiu; Dumitrache, Florian; Morjan, Ion
Abstract: Current study presents experimental results concerning dynamic contact angle of water-FeC nanofluid on three solid surfaces what are frequently used in practical applications involving heat transfer, namely aluminum, copper and stainless steel. Hence, measurement of both advancing and receding contact angles were carried out by the Wilhelmy plate procedure for each surface within a range of temperatures values from 20 °C to 50 °C, and three nanoparticles mass concentrations (0.1%, 0.5% and 1.0%). Results reveal the dynamic contact angles decrease with the temperature, the reduction in the average contact angle of aluminum–FeC nanofluid being more significant than of copper-FeC nanofluid and stainless steel–FeC nanofluid, showing that aluminum–FeC nanofluid exhibits better wettability. In addition, it was noticed a reduction of the average contact angle with the nanofluid concentration. The results contribute to a better comprehension of the nanoparticles influence in the surfaces wettability.